Huzur Temsilleri: Performances in the Ottoman Palace in the Presence of the Sultans - Nilgün Firidinoğlu (Konservatoryum)
Tulûat and Ortaoyunu, which are important elements of the entertainment culture of the people in the Ottoman Empire, appear as theatrical genres frequently preferred by the Palace. In this study, Tulûat and Ortaoyunu performances performed in the presence of the sultan in the last quarter of the nineteenth century will be discussed in the context of the relationship between the audience and the actors and the impact of this relationship on the quality of the representation.First of all, the concept of Huzur Temsilleri, meaning “performances in the presence of the sultan” will be explained. The structure of the Muzıka-yi Hümâyun, the institutional framework of the representations in the palace, and the admission processes of the players to this institution will be discussed. The effect of appearing before the sultan on the identity of the actor and the decisive role of power in shaping the performance will then be analyzed. The contradictions between the demands of the palace and the dynamics of the Tulûat theater (the improvised theater) will be evaluated through examples, and the performance time, duration, content, and the interaction of the actor with the power/spectator sultan will be analyzed with various examples throughout the study.